Re-examination of the standards for transit oriented development influence zones in India - Sangeetha Ann; Meilan Jiang; Toshiyuki Yamamoto (Journal of Transport and Land Use)
Transit oriented development (TOD) is a land-use and transport integrated urban planning strategy that is highly acclaimed for promoting sustainable city development. This review aims to identify the problems regarding adoption of TOD standards or guidelines formulated by developed countries in developing countries, such as India, and the necessity of conducting adaptability studies on TOD influence areas. The existing studies show that the size of the influence area varies among different cities and travel modes. Accordingly, no single size influence zone is suitable for all cases. This review highlights the necessity of carefully considering the spatial extent of influence areas and modes other than walking as access or egress modes in the Indian context. Moreover, this review aims to provide insight on how to plan TOD in the context of developing countries, because the mobility patterns in these countries differ considerably from those in the developed world.